Restricted partitions - Rafael Jakimczuk (International Journal of Mathematics and Mathematical Sciences)
We prove a known partitions theorem by Bell in an elementary and constructive way. Our proof yields a simple recursive method to compute the corresponding Sylvester polynomials for the partition. The previous known methods to obtain these polynomials are in general not elementary.